The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1139/cjpp-2016-0147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fisetin on hyperhomocysteinemia-induced experimental endothelial dysfunction and vascular dementia

Abstract: This study was designed to investigate the effects of fisetin (FST) on hyperhomocysteinemia (HHcy)-induced experimental endothelial dysfunction (ED) and vascular dementia (VaD) in rats. Wistar rats were randomly divided into 8 groups: control, vehicle control, l-methionine, FST (5, 10, and 25 mg/kg, p.o.), FST-per se (25 mg/kg, p.o.), and donepezil (0.1 mg/kg, p.o.). l-Methionine administration (1.7 g/kg, p.o.) for 32 days induced HHcy. ED and VaD induced by HHcy were determined by vascular reactivity measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…These higher levels of Hcy in PDD/VPD patients may damage neuron and vascular endothelial cells in the brain, inducing neuroinflammation [ 23 , 65 , 66 ]. High levels of Hcy could break down the blood brain barrier (BBB) and lead to cerebrovascular dysfunction, which subsequently modulates the activities of enzymes and neuropeptides and influences hippocampal volume in the pathophysiological processes of dementia [ 67 - 69 ]. It has been shown that Hcy could stimulate superoxide and hydrogen peroxide generation in vivo and in vitro [ 70 ] and that ChEs activities are inhibited by high level of Hcy mediated by the generation of free radical formation [ 71 - 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…These higher levels of Hcy in PDD/VPD patients may damage neuron and vascular endothelial cells in the brain, inducing neuroinflammation [ 23 , 65 , 66 ]. High levels of Hcy could break down the blood brain barrier (BBB) and lead to cerebrovascular dysfunction, which subsequently modulates the activities of enzymes and neuropeptides and influences hippocampal volume in the pathophysiological processes of dementia [ 67 - 69 ]. It has been shown that Hcy could stimulate superoxide and hydrogen peroxide generation in vivo and in vitro [ 70 ] and that ChEs activities are inhibited by high level of Hcy mediated by the generation of free radical formation [ 71 - 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…The highest concentration of fisetin was found in strawberries followed by apple and persimmon [ 18 ]. Fisetin has been the topic of research in current years due to its anticancer, anti-inflammatory, memory-enhancing, and neuroprotective properties [ 19 ]. Fisetin has also been discovered to have substantial antioxidant capabilities in membrane settings, and it has been proposed as a possible treatment agent for a variety of free radical-mediated disorders [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fisetin has also been discovered to have substantial antioxidant capabilities in membrane settings, and it has been proposed as a possible treatment agent for a variety of free radical-mediated disorders [ 20 ]. Previous studies also showed the neuroprotective effects of Fisetin in experimental models of dementia induced by hyperhomocysteinemia [ 19 ] as well as of occlusion of the middle cerebral artery (MCAO) [ 21 ]. It was well known that the antioxidant effects of fisetin could be attributable to the activation of Nrf2/HO-1 [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that FST inhibits inflammation related cytokines like TNF-a, IL-6, and NF-kB in streptozotocin (STZ)-induced diabetic cardiomyopathy rats (Althunibat et al, 2019). FST has also been shown to upregulate glutathione (GSH) in isoproterenol-induced cardiac ischemic injury rats and hyperhomocysteinemia-induced endothelial dysfunction rats (Hemanth Kumar et al, 2017;Garg et al, 2019). Thanks to its chemical structure ( Figure 1A), FST has an electron donating capacity to scavenge free radicals, which could have implications for diseases caused by oxidative stress (Khan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%